Turnover intention among manufacturing industry employees in Malaysia : an analysis using structural equation modeling (SEM) - Gopal Perumal,; Suguna Sinniah,; Ramesh Kumar Moona Haji Mohamed,; Kok, Pooi Mun; Uma Murthy, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This research paper explores the turnover intention among manufacturing industry employees in Malaysia. Four variables were studied: role overload, role ambiguity, role conflict, and work-family conflict. The survey results collected from 153 employees from manufacturing companies in Malaysia. The analysis been obtained via SEM-PLS. Total four hyphotheses were tested. Positive results obtained for role overloaded towards turnover intention. Negative results obtained for role ambiguity, role conflict, and work-family conflict. Based on the findings all the manufacturing recognize importance of staff retention for superior value for an organization.